Partisipasi Pesantren Luhur Al-Husna dalam Perdamaian Nasional: Studi tentang Peran Pesantren di Surabaya - Setianingsih, Dwi; Yusuf, M. (FIKRAH, 2021)
This article aims to discuss and see further how big the role of the students of the Luhur Al-Husna Islamic Boarding School when facing plurality, both related to religious differences and certain sects. To answer these objectives, this article uses qualitative research with the type of phenomenology with analysis using the theory of Peter L. Berger and Thomas Luckman which includes externalization, objectification, and internalization. In instilling the value of peace in students, the Luhur Al-Husna Islamic Boarding School has two directions: namely, through the dawuh of Kiai Ali Maschan and through the customization ethics of the pesantren. Both of these are part of verbalization. While the teachings of the yellow book, have a secondary influence or role in cultivating the value of peace for Al-Husna students. These two things are external aspects in the pesantren that are understood and objectified into a general truth, that the Luhur Al-Husna Islamic Boarding School is a pesantren of "Peace." Then the value of peace is internalized in morals and behavior which leads to activities and taking roles in peace organizations and groups.